ANALISIS KEBUTUHAN LABORATORIUM VIRTUAL BERBASIS PROYEK SEBAGAI MEDIA BELAJAR PADA TOPIK GRAVIMETRI - Julianingsih, Nia Laras; Situmorang, Manihar; Jullianingsih, Nia Laras (UIN AR-RANIRY, 2025)
The willingness of practicum is an important component in gravimetry learning which is procedural and involves scientific skills. The purpose of this study is to determine and evaluate UNIMED chemistry students' requirements for project-based virtual labs. This study employs a descriptive methodology that combines qualitative and quantitative techniques using gravimetry-related questionnaires and interviews. One lecturer and twenty-four chemistry study program participants who had completed analytical chemistry courses made up the study's respondents. Interview sheets, Google Forms-distributed requirements analysis questionnaires, and questionnaires examining utilized learning media were among the research tools. Descriptive data analysis was used to determine the needs of the students. The study's findings show that because gravimetry materials lack real laboratories, students require learning resources in the form of virtual laboratories as supporting media. The results of the interviews indicated that students were receptive to the creation of virtual laboratories. The needs analysis conducted through questionnaires revealed that students had a high demand for the creation of virtual laboratories, with media needs accounting for 82.50%, visualization and simulation for 85%, projects for 63.06%, and virtual laboratories for 75.17%. With a percentage of 60.66%, the findings of the examination of educational materials utilized in gravimetry instruction are classified as good.